2023
DOI: 10.1101/2023.02.15.528757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oncogenic KrasG12Dspecific non-covalent inhibitor reprograms tumor microenvironment to prevent and reverse early pre-neoplastic pancreatic lesions and in combination with immunotherapy regresses advanced PDAC in a CD8+T cells dependent manner

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is associated with mutations in Kras, a known oncogenic driver of PDAC; and the KRASG12D mutation is present in nearly half of PDAC patients. Recently, a non-covalent small molecule inhibitor (MRTX1133) was identified with specificity to the KrasG12D mutant protein. Here we explore the impact of KrasG12D inhibition by MRTX1133 on advanced PDAC and its influence on the tumor microenvironment. Employing different orthotopic xenograft and syngeneic tumor models, eight diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Together, these data indicate that AMG 510 treatment engenders an anti-tumor immune profile, reminiscent of the changes in immune populations in KRAS G12D -driven tumors treated with MRTX1133 (17,44). However, the lack of obvious KRAS inhibition-induced tumor regression in the K C PC model, in contrast to KRAS G12D -driven models, implicates that cancer cells can sustain viability in a relatively 'hot' anti-tumor immune microenvironment.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Together, these data indicate that AMG 510 treatment engenders an anti-tumor immune profile, reminiscent of the changes in immune populations in KRAS G12D -driven tumors treated with MRTX1133 (17,44). However, the lack of obvious KRAS inhibition-induced tumor regression in the K C PC model, in contrast to KRAS G12D -driven models, implicates that cancer cells can sustain viability in a relatively 'hot' anti-tumor immune microenvironment.…”
Section: Resultsmentioning
confidence: 83%
“…3A-B). Recent studies in preclinical models demonstrated that the reprogramming of immune microenvironment, in particular the activation of cytotoxic T cells, is critical for the regression of Kras G12D -driven tumors following MRTX1133 treatment (17,44).…”
Section: Resultsmentioning
confidence: 99%
“…To this date published data regarding MRTX1133 showed efficacy against only KRAS G12D and effect on T cells. (30, 3439)…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been noted with KRAS G12C (18, 35) and KRAS G12D -specific inhibitors (36), which demonstrated either that T cells contribute to the efficacy of targeted mutation-specific KRAS inhibitors or are critical for their long-term control of regrowth from metastatic disease (36). Furthermore, the presence of T cells predicted the response to PD-1 immune checkpoint blockade in preclinical models of NSCLC and PDA (35, 48, 49).…”
Section: Discussionmentioning
confidence: 99%
“…This data suggests that these models reflect different levels of activation of T cells most notably in 2838c3 model system, which has considerably more putative neoantigens than 7160c2 and increased proportion of CD103 + DCs (34). Diversity within KPC tumor clones is attributed in part to epigenetic patterns of gene expression, such as CXCL-1, which in turn influence the composition and function of immune cells in the TME, has been noted and can also impact growth responses to immune checkpoint blockade (34, 48, 49). Although these differences are more pronounced between models and those with evidence of increased T cell infiltration and function, it is likely that myeloid and T cell responses will vary among preclinical tumor models due to variations in tumor epigenetics that impact the local immune microenvironment (35, 36).…”
Section: Discussionmentioning
confidence: 99%